Is doppler ultrasonography reliable in the evaluation of solid testicular lesions? (Annals of Medical Research, 2021)
Aim: Evaluation of using color Doppler ultrasonography in the diagnosis of testicular solid lesions. The aim of our study was to determine the rate of benign lesions in patients with hypervascularized solid intratesticular lesions. Material and Methods: The data of 88 patients who underwent inguinal orchiectomy and who were diagnosed to have a scrotal mass in color Doppler ultrasound examination between March 2013 and March 2018 were retrospectively evaluated. All patients’ age, complaints during their admission to hospital, size of solid lesions, preoperative tumor markers (AFP, bHCG and LDH) and post operative pathology results were evaluated. Two-tailed tests were used to determine the value of preoperative numerical parameters and Fisher’s exact test to compare preoperative non-numerical parameters of both malignant and benign solid lesions, and p0.05 was considered significant.Results: The mean age of the patients was 38.54±19.09 years. The mean lesion size was 4.21±2.65 cm. The high levels of tumor markers (AFP, bHCG, LDH) were detected in 24 (27.2%) patients before the operation. In 72 patients, the size of the lesion was greater than 1 cm and in 16 patients it was less than 1 cm. As a result of the pathological evaluation of the testicular masses, it was found that 29 (32.9%) were malignant and 59 (67.1%) were benign. High levels of tumor markers, palpability and large solid lesion size were found as parameters predicting malignancy.Conclusion: In the evaluation of testicular masses with scrotal USG and Doppler USG, the rate of benign mass detection is relatively higher. In small masses, non-palpable masses and in patients with no tumor marker elevation, testicular biopsy or testicular preventive surgery should be considered.
Keywords: Doppler; testis; tumour; ultrasound